Data science your first day - Deza, Alfredo (Pragmatic AI Solutions, 2022)
Perform Data Science on Day One! 00:00 Intro 02:02 Data Science Project Structure Overview 05:15 Create Github Repo 07:28 Launch Github Codespaces 11:34 Using Colab Notebook 12:47 Using TOC in Colab Notebook 14:43 Saving notebook to Colab to Github 19:52 Ingesting CSV files into Colab 22:31 Describing Data using df.describe() 24:30 Plotting data with seaboard 28:30 lmplot 29:30 Comparing cumulative deaths in Covid19 plot by state 32:40 Merging Pandas Dataframe with election and Sugar Consumption 37:38 Exporting CSV file and uploading to Github from Colab result 39:27 Continuous Integration of Jupyter Notebook with Github Actions 40:44 Create Makefile 44:32 Using Github Actions to test Jupyter via nbval plugin 45:43 Using Github Status Badge for Jupyter Notebook test run pass.